2017
DOI: 10.1007/s00277-017-3168-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing platelet transfusion refractoriness in patients undergoing allogeneic hematopoietic stem cell transplantation

Abstract: Hematopoietic stem cell transplantation has been considered a risk factor for development of platelet transfusion refractoriness. The objective of this study was to assess the platelet transfusion refractoriness rate in patients undergoing allogeneic hematopoietic stem cell transplantation from different sources. We retrospectively reviewed the charts and transfusion records of patients who underwent allogeneic stem cell transplantation at our institution between 2013 and 2015. The evaluation of post-transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…Of the total 5840 platelet transfusions given to 185 adults, 3196 transfusions (54.7%) with 16-hour CCI <4.5 × 10 9 /L were associated with a poor transfusion response, indicating that PTR was a relatively common problem in adult patients undergoing CBT. This is consistent with a previous report [10]. Risk factors for PTR included the following: presence of HLA class I antibody, lower CB TNC dose, lower CB CD34 + cell dose, 3 locus HLA disparities, body temperature ≥38°C, CRP ≥10 mg/dL, CMV reactivation, use of foscarnet, and use of liposomal amphotericin B.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Of the total 5840 platelet transfusions given to 185 adults, 3196 transfusions (54.7%) with 16-hour CCI <4.5 × 10 9 /L were associated with a poor transfusion response, indicating that PTR was a relatively common problem in adult patients undergoing CBT. This is consistent with a previous report [10]. Risk factors for PTR included the following: presence of HLA class I antibody, lower CB TNC dose, lower CB CD34 + cell dose, 3 locus HLA disparities, body temperature ≥38°C, CRP ≥10 mg/dL, CMV reactivation, use of foscarnet, and use of liposomal amphotericin B.…”
Section: Discussionsupporting
confidence: 91%
“…However, some patients do not achieve the expected platelet count increment after platelet transfusion. Several studies have demonstrated that platelet transfusion refractoriness (PTR) is common after allogeneic HCT [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we could not consider him to have had a response per protocol, there was some evidence suggesting a clinical benefit as he also met the 10–60 min CCI > 7 500 and 18–24 h CCI > 5 000 after the third and fourth transfusion of platelets given after eculizumab treatment (Table SII). Since only 10 patients were treated in our trial, the study was not powered to estimate the response rate precisely and is unable to identify unique patient characteristics leading to refractoriness and factors predicting response to eculizumab (Slichter et al , ; Solves et al , ). Nevertheless, the resolution of platelet refractoriness in a subset of responding patients treated with eculizumab provides proof of concept and data supporting complement as playing a pathophysiologic role in platelet refractoriness.…”
Section: Discussionmentioning
confidence: 99%
“…A difference has been reported in CCI depending on the type of stem cell source. There was a higher rate of PTR in patients who received umbilical cord blood transplantation (UCBT) as compared to patients who received peripheral blood stem cell transplantation (PBSCT) . Here, we could not assess the effect of stem cell source because the number of patients given cells from each stem cell source was limited, and the variance of CCI‐24 between each patient was large.…”
Section: Discussionmentioning
confidence: 99%